Seasonal Variation in the Free Amino Acids in Gut Contents during Developmental Stages of Antheraea proylei Jolly (Saturniidae: Lepidoptera) - Kumar2, M. Chinamen1*, Ok. Monoroma2; M. (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The qualitative analysis of free amino acids has been done in the gut contents of Antheraea prolylei during its developments stages. The collection of gut contents from the first instar larvae was not possible the physiological experiment could not be done. The second instar larvae showed the presence of 8, 7 and 5 amino acids in spring, summer and autumn season respectively. The third instar larvae revealed the presence of 9, 8 and 5 ninhydrin positive spots in spring, summer and autumn seasons. The fourth instar larvae showed the presence of 10, 9 and 7 amino acids in spring, summer and autumn seasons while the fifth instar larvae exhibit 11, 9 and 8 amino acids in spring, summer and autumn season respectively.